ANALYSIS THE ABILITY OF PROFIT AND CASH FLOW INFORMATION IN PREDICTING FUTURE CASH FLOWS - Miranti Pangestu (Universitas Airlangga, 2020)
The purpose of this study is to examine whether earnings information or cash flow information can predict future cash flows in service companies in Indonesia. The sample determined in this study, using the purposive sampling method, produced 145 companies listed on the Indonesian Stock Exchange in 2015-2017, with a total of 435 observations. In this study, multiple regression analysis techniques are used. The results shown by the t-test are partially significant net income. In this case, net income is a predictor of future cash flows. Whereas cash flow information namely operating cash flow, investing cash flow, and funding cash flow do not affect the future cash flow